2006
DOI: 10.1007/s10974-006-9066-5
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of muscle fibers reconstituted in the regeneration process of masseter muscle in an mdx mouse model of muscular dystrophy

Abstract: Mdx mice, which lack dystrophin, were examined for changes in the properties of muscle fibers in the growth process of the masseter muscle at the morphological, protein and transcriptional levels. The slow-type isoform, MyHC-1, and the fast-type isoforms, MyHC-2a, MyHC-2d and MyHC-2b, were examined at the protein and the transcriptional level. Morphological examination showed that in the mdx mouse masseter muscle, degeneration, necrosis, and regeneration occurred, particularly at the age of 4 weeks, and many r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
0
21
0
1
Order By: Relevance
“…It was reported that, in somite-derived muscles of the extremities, muscle necrosis began at 2 weeks after birth, immediately followed by regeneration, and the majority of necrotic muscles became regenerated at 4 weeks after birth (Dangain et al 1984;DiMario et al 1991;Attal et al 2000). A similar phenomenon was noted in the branchial arch-derived mdx mouse masseter muscle (Lee et al 2006), and cell degeneration in this muscular dystrophy was ascribed to the lack of dystrophin, resulting in damage to cell membrane stability, leading to excessive influx of calcium ions into muscle cells, a mechanism similar to that of necrosis.…”
Section: Introductionmentioning
confidence: 58%
“…It was reported that, in somite-derived muscles of the extremities, muscle necrosis began at 2 weeks after birth, immediately followed by regeneration, and the majority of necrotic muscles became regenerated at 4 weeks after birth (Dangain et al 1984;DiMario et al 1991;Attal et al 2000). A similar phenomenon was noted in the branchial arch-derived mdx mouse masseter muscle (Lee et al 2006), and cell degeneration in this muscular dystrophy was ascribed to the lack of dystrophin, resulting in damage to cell membrane stability, leading to excessive influx of calcium ions into muscle cells, a mechanism similar to that of necrosis.…”
Section: Introductionmentioning
confidence: 58%
“…Muscle proteins, which contribute to the structure of myoblasts, normally show turnover through new synthesis and degradation (Okubo et al, 2006;Lee et al, 2006;Suzuki et al, 2007). Any imbalance between synthesis and degradation results in an increase or decrease in muscle volume; for example, promotion of the synthesis pathway or inhibition of the degradation pathway in myoblasts will cause an increase in muscle proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that, in somite-derived muscles of the extremities, muscle necrosis began at 2-week after birth, immediately followed by regeneration, and the majority of necrotic muscles became regenerated at 4-week after birth (Dangain et al, 1984;DiMario et al, 1991;Attal et al, 2000). A similar phenomenon was noted in the branchial arch-derived mdx mouse masseter muscle (Lee et al 2006), and cell degeneration in this muscular dystrophy was ascribed to the lack of dystrophin, resulting in damage to cell membrane stability, leading to excessive influx of calcium ions into muscle cells, a mechanism similar to that of necrosis. Thus, mdx mice have been used as a model to study the mechanism of muscle necrosis and regeneration (Gillis, 1996).…”
Section: Discussionmentioning
confidence: 55%